Secondary orthostatic tremor in the setting of cerebellar degeneration. (May 2016) - Sarva, Harini; Severt, William Lawrence; Jacoby, Nuri; Pullman, Seth L.; Saunders-Pullman, Rachel
Highlights: Orthostatic tremor causes a fast high frequency leg tremor upon standing, not with sitting. Orthostatic tremor coexisting with cerebellar ataxia was reported once before but never with SCA-2. Anti-tremor medications (propranolol) can be considered a treatment option. Abstract: Orthostatic tremor (OT) and cerebellar ataxia are uncommon and difficult to treat. We present two patients with OT and cerebellar degeneration, one of whom had spinocerebellar ataxia type 2 and a good treatment response.